Can we be engineers of property rights to natural resources? some evidence of difficulties from the rural areas of Zimbabwe - Luckert, M.A. (2001)
The desire for research to be policy relevant has caused many social science studies to have “engineering” dimensions. With respect to the engineering of property rights, economic approaches indicate that we require knowledge regarding the makeup of current property rights structures, how changes to current structures affect the use and management of natural resources, and how property rights have evolved. In the case of rural areas of Zimbabwe, research has largely disclosed complexities involved in addressing these questions, but it has not yet provided sufficient information needed to pursue property rights engineering objectives. The difference between what we know and what we need to know provides the basis for a research agenda that will require some significant changes in the way that property rights are described and analyzed.